Model kritičnih dejavnikov uspeha uvajanja rešitev SAP in Navision - Sternad Zabukovšek, Simona (Naše gospodarstvo, 2007)
Implementation of enterprise resource planning solutions (ERP solutions) is a complicated task because of its complexity. Organizations must start implementation deliberately and have to take into consideration the implementation methodology of an ERP vendor. The study of factors (CSF) which influence the success of the implementation of ERP solutions is important because of several unsuccessful implementation attempts. Research conducted in Slovenian organizations has shown that implementation method did not have any influence on the importance of CSF, that there is a connection between CSFs within each vendor implementation method, and that there are differences in importance of CSFs within each vendor methodology.
Keywords: podjetja; elektronsko poslovanje; informacijska tehnologija; information technology; informacijski sistemi; informatika; information science; uvajanje